Human papillomavirus (HPV) infection and vaccines: Knowledge, attitude and perception among female students at the University of Lagos, Lagos, Nigeria - Christian Chigozie Makwe; Rose Ihuoma Anorlu; Kofoworola Abimbola Odeyemi (Journal of Epidemiology and Global Health, 2019)
Aim: This study sought to determine knowledge of and attitude towards human papillomavirus (HPV) infection, HPV-related diseases and HPV vaccines among female undergraduate students at the University of Lagos. Methods: A self-administered questionnaire was administered between May and July 2010, to 368 female students aged 16–29 years, who were selected from two faculties of the University of Lagos using two-stage sampling method. Data collected included: socio-demographic characteristics, sexual history, awareness and knowledge of HPV infection, cervical cancer and genital warts, and HPV vaccine; the perceived risk of acquiring genital HPV infection and developing cervical cancer or genital warts, and the willingness to receive an HPV vaccine. Results: Only 64 (17.7%) and 52 (14.4%) of the students had ever heard of HPV infection and HPV vaccines respectively. The median HPV knowledge on a 15-item score was 2. Overall, only 11.1% knew that genital HPV infection can cause cervical cancer. Fourteen (6.9%) of those who were aware of cervical cancer agreed they were at risk of developing the disease. Of the 52 students who had heard of the HPV vaccine, 24 (46.2%) knew it was given for cervical cancer prevention and 30 (57.7%) expressed their willingness to receive the vaccine. Conclusion: The knowledge of and the perceived susceptibility to HPV infection and HPV-related diseases among female students in the University of Lagos were generally low. The need for a well-designed HPV-educational program to bridge the knowledge gap cannot be overemphasized.